TEKS DRAMA GONG I MADE SUBANDAR HASTA KOMALA ANALISIS BENTUK, FUNGSI, DAN MAKNA - Pertiwi, Putri (Humanis; Volume 11. No3. Juni 2015)
Research on the " Text Drama Gong I Made Subandar Hasta Komala Analysis Form , Function , and Meaning " , aimed to describe the structure of the building as well as the text examines the function and meaning of the text contained in the drama gong " I Made Subandar Hasta Komala " . This research uses , semiotic theory ( Enraswara , 2008: 64 ) , the theory of the structure , ( Teeuw , 1984: 135 ) . The method used in the stage of providing data using methods refer to the technical note . In addition, using interviews with recording techniques and record . Furthermore, in the stage of data analysis using descriptive analytic techniques are also used literally and idiomatically . At the stage of presentation of the data , the method used is an informal method of inductive and deductive techniques . The results showed that ; ( 1 ) analyzes the structure of the text form of drama that builds drama gong " I Made Subandar Hasta Komala " There are four , namely : prologue , stage , scenes , and dialogue , and the narrative structure of the play there are five: plot , characterization and characterization , setting , theme , and mandate , ( 2 ) the language and style of the language used in the text of the drama gong " I Made Subandar Hasta Komala " ( 3 ) text functions drama gong " I Made Subandar Hasta Komala " there are some functions that are contained in each babaknya quote quote that reflects situation or social reality . ( 4 ) the meaning of the text drama gong " I Made Subandar Hasta Komala " This is a search for identity .
Keywords: Text , Drama Gong , Nyineb Wangsa